Yearning for Words, Learning With Words: Poetic Ruminations (LEARNing Landscapes, 2011)
As a poet I am always seeking ecological interconnections amidst body, brain, language, knowing, mind, consciousness, education, imagination, heart, cognition, and spirit. In language play I hope to find my way to a purposeful pedagogy that acknowledges and honours how learning is always a holistic adventure in process and flux, an adventure of human becoming filled with wonder and mystery beyond the counting, but always abundantly available for courting with wild delight and desire.
Keywords: poet; ecological connection; body; brain; language; mind; knowing; consciousness; edcuation; imagination; heart; cognition; spirit; pedagogy; learning